Green-Solvent Extraction and Antioxidant Evaluation of Muntingia calabura L. Flowers Using the DPPH Free Radical Scavenging Method - Nurmaya Effendi; St Maryam; Muh Rezky Hadi Wijaya (Pharmaceutical Reports, 2026)
Kersen (Muntingia calabura L.) flowers are known to contain bioactive compounds such as flavonoids and tannins, which contribute to various pharmacological activities, including anticancer, antidiabetic, and antioxidant effects. Antioxidants play a crucial role in preventing or slowing oxidative damage by neutralizing free radicals. This study aimed to evaluate the antioxidant activity of aqueous extracts of Muntingia calabura L. flowers using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method. The extraction process was carried out using Microwave-Assisted Extraction (MAE) with a green solvent approach. The antioxidant activity was analyzed using a UV–Visible spectrophotometer, and the results were expressed as the half-maximal inhibitory concentration (IC₅₀), with quercetin used as a reference standard. The results showed that the Muntingia calabura flower extract exhibited strong antioxidant activity, with an IC₅₀ value of 15.81 µg/mL, which falls within the category of very strong antioxidants (50 µg/mL). In conclusion, the aqueous extract of Muntingia calabura L. flowers demonstrates significant antioxidant potential and may serve as a promising natural source of antioxidants for further development in pharmaceutical or nutraceutical applications.